Efficacy & safety of brolucizumab 6.0 mg versus 3.6 mg in diabetic macular edema - Sanjay Kumar Mishra; Pradeep Kumar; Amrita Joshi; Aman Saraf; Abhijeet Awasthi; Supriya Dhar; Khaleel M; Atul Kumar; Vipin Rana; Ravi D (International Journal of Retina and Vitreous)
Abstract Background Management of Diabetic Macular edema (DME) requires repeated injections. Therefore newer Anti-VEGFs like Brolucizumab with longer durability have been introduced. We compared two different dosages of Brolucizumab, 6.0 mg and 3.6 mg, for their safety & efficacy in treatment of DME, in treatment naïve patients over 52 weeks. Method A prospective, pilot randomised controlled, single centre, double blinded, two arm comparative study was conducted between Dec 2022 to Apr 2024. The study recruited 82 patients of DME who were randomised into two groups of 41 patients each, one group to be treated with Brolucizumab 6.0 mg in 50 μL and the other to receive 3.6 mg in 30 μL. All patients received the first dose of Brolucizumab at 0 week and were then followed up at every 4 weeks for detailed ophthalmic and OCT macula examination. Those who met the pre-defined re-treatment criteria were re-injected with Brolucizumab, the dose being fixed for each group throughout the study. All patient receiving an injection were further followed up on Day 1, Day 7 and Day 28 to look for any adverse reactions. The efficacy parameters included change in best corrected visusal acuity (BCVA), contrast and central macular thickness (CMT) on Optical Coherence Tomography. The average number of injections recd in each group were also calculated. Results The change in BCVA from baseline in 6.0 mg group was 0.54 LogMAR units and 3.6 mg group was 0.59 LogMAR units, which was not statistically significant. The reduction in CMT from baseline in 6.0 mg group was 133.2 µm (μ) and 3.6 mg group was 110.6 μ, which was not statistically significant. The improvement in contrast from baseline in 6.0 mg group was 0.74 and 3.6 mg group was 0.95, with p value of 0.0002. The re-injection interval was 14.21 weeks in 6.0 mg group and 15.56 weeks for 3.6 mg subgroup. The total number of adverse events in both groups were similar at 70 in 6.0 mg group and 47 in 3.6 mg group with only one grade 4 adverse event occurring in each group. Conclusion The results of present study show that the safety and efficacy of both doses of Brolucizumab, i.e. 6.0 mg and 3.6 mg, for treating diabetic macular edema is similar. Trial registration Study was registered with Clinical trials registry of India (CTRI ref no. CTRI/2023/06/054105), registered on 14 Nov 2022.